THE CONTRIBUTION OF VILLAGE SAVINGS LOAN ASSOCIATION(VSLA)TO THE GROWTH OF WEMAN'S ENTERPRISES IN NANTABULIRWE PARISH,MUKONO DISTRICT. - JUAN SUSAN MARTIN (UGANDA CHRISTIAN UNIVERSITY, 2024)
The study looked at how the Village Savings Loan Associations (VSLA) in Nantabulirwa parish, Mukono district, helped women's businesses flourish. The following goals guided the study: To determine how loan availability affected the expansion of women's microbusinesses in Nantabulirwa parish, Mukono district; To investigate the impact of training and group support on the expansion of women's microbusinesses in Nantabulirwa parish, Mukono district; and To determine the impact of savings on the expansion of women's microbusinesses in Nantabulirwa parish, Mukono district. This study used a quantitative technique using a survey research design. This study used a quantitative technique using a survey research design. The study's total mean score of 3.65 showed that most people agreed that loans have a beneficial influence. The respondents concurred that VSLA loans promoted financial independence (mean 4.00), facilitated investment in productive assets (mean 3.33), and boosted business growth (mean 3.67). There was a high degree of agreement about group systems promoting growth (mean 3.75) and financial literacy facilitating informed judgments (mean 4.03). Entrepreneurial development was aided by VSLA participation (mean 3.81); however, finance availability was restricted due to illiteracy (mean 3.58). Gender-related workshops received favorable reviews (mean 3.83). The study found that through easily accessible loans, training/group assistance, and savings mobilization, VSLAs play a vital role in the establishment of women's microenterprises in Nantabulirwa Parish. Despite obstacles, loans promote asset investment and financial independence; training improves decision-making and skill sets; and savings allow for growth and profitability. As demonstrated by increased revenues and clientele among participants, these factors work together to combat poverty and advance gender parity.Full potential is hampered by issues including gender bias, literacy shortages, and collateral requirements, which emphasizes the need for focused initiatives.
UNDERGRADUATE RESEACH